Private equity investment committee paper on Pestana Hotel Group - contingency plan and exit strategy - Rocha, Tomás Antunes (2020)
This Work Project, taken in the context of a Private Equity Challenge, was developed by a group of four Nova Master’s in Finance students to meet only academic purposes and consists on a simulation of an Investment Committee Paper on Pestana Hotel Group. As the Portuguese based Group was the target of the developed project, the work covers all the qualitative and quantitative aspects of the company. A possible strategy, focusing on the operational side of the Hospitality segment, appears as an attractive Private Equity investment. This specific part focuses on the chapters of the contingency plan and exit strategy.